2018
DOI: 10.1590/s0102-865020180020000009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aquaporin 4 and inward rectifier potassium channel 4.1 on medullospinal edema after methylprednisolone treatment to suppress acute spinal cord injury in rats

Abstract: Effects of aquaporin 4 and inward rectifier potassium channel 4.1 on medullospinal edema after methylprednisolone treatment to suppress acute spinal cord injury in rats 1 9-Experimental SurgeryActa Cir Bras. 2018;33(2):175-184 AbstractPurpose: To investigate the effects of aquaporin 4 (AQP4) and inward rectifier potassium channel 4.1 (Kir4.1) on medullospinal edema after treatment with methylprednisolone (MP) to suppress acute spinal cord injury (ASCI) in rats. Methods: Sprague Dawley rats were randomly divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…Curiously, Cabrera-Aldana et al [17] demonstrated the largest increase in oedema after treatment with methylpredinoslone (MP) (100% above the sham and control group). However, in contrast, Li et al [33] reported 72.2% attenuation after MP treatment at 7 days after SCI. Moreover, Liu et al [27], Ge et al [28] and Li et al [32] reported no significant difference in spinal cord water content or AQP4 expression levels at 12 h, but did show a difference at 24 h after treatment.…”
Section: Results Of Individual Studiesmentioning
confidence: 88%
See 4 more Smart Citations
“…Curiously, Cabrera-Aldana et al [17] demonstrated the largest increase in oedema after treatment with methylpredinoslone (MP) (100% above the sham and control group). However, in contrast, Li et al [33] reported 72.2% attenuation after MP treatment at 7 days after SCI. Moreover, Liu et al [27], Ge et al [28] and Li et al [32] reported no significant difference in spinal cord water content or AQP4 expression levels at 12 h, but did show a difference at 24 h after treatment.…”
Section: Results Of Individual Studiesmentioning
confidence: 88%
“…Although each study investigated a different therapeutic, mechanistically, nearly all reported the modulation of AQP4. Not only was downregulation or the subcellular relocalisation of AQP4 a hallmark of an effective oedema treatment, the degree of oedema attenuation determined the extent of functional recovery [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. To complement these findings, the majority of studies also measured locomotor activity, glial activity using GFAP immunoreactivity and visualised the lesion site using IHC or other imaging techniques in an attempt to understand the anti-oedemic action of the novel treatments as well as the complex pathophysiology behind the development of oedema.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations